2008
DOI: 10.1007/s10661-008-0570-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of noise pollution levels in some selected areas in Ilorin Metropolis, Nigeria

Abstract: The noise pollution is a major problem for the quality of life in urban areas. This study was conducted to compare the noise pollution levels at busy roads/road junctions, passengers loading parks, commercial, industrial and residential areas in Ilorin metropolis. A total number of 47-locations were selected within the metropolis. Statistical analysis shows significant difference (P < 0.05) in noise pollution levels between industrial areas and low density residential areas, industrial areas and high density a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 7 publications
0
22
1
Order By: Relevance
“…Singh and Jain (1995) reported that the measurements of noise levels in residential, industrial and commercial areas in the capital city of India, Delhi commercial areas have the highest noise levels followed by industrial and residential areas. This is contrary to the finding of Oyedepo and Saadu (2009) who carried out measurement of noise levels in busy road junctions, residential, industrial, commercial and passenger loading parks areas in Ilorin city, Nigeria. The result shows that industrial areas have the highest noise levels followed by busy roads and junctions, passengers loading parks and commercial areas.…”
Section: Introductioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Singh and Jain (1995) reported that the measurements of noise levels in residential, industrial and commercial areas in the capital city of India, Delhi commercial areas have the highest noise levels followed by industrial and residential areas. This is contrary to the finding of Oyedepo and Saadu (2009) who carried out measurement of noise levels in busy road junctions, residential, industrial, commercial and passenger loading parks areas in Ilorin city, Nigeria. The result shows that industrial areas have the highest noise levels followed by busy roads and junctions, passengers loading parks and commercial areas.…”
Section: Introductioncontrasting
confidence: 96%
“…The need for studies regarding urban noise pollution and its consequences on the environment has motivated various researchers in several countries (Ugwunyi et al, 2005;Oyedepo and Saadu, 2009). Many researchers have reported that road traffic is the predominant noise source in urban areas (Bisio, 1996;Nelson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, several noise pollution guidelines have been developed. In sub-Saharan Africa, although, where noise legislations exist, they are often poorly enforced and implemented (Sonibare et al 2004; Chung et al 2005; Oyedepo and Saadu 2009; Sørensen et al 2011; Oyedepo 2012). However, interest may be attributed to the current development of guidelines and standards for environmental pollution by the Federal Environmental Protection Agency (FEPA 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Noise pollution is not only the growing problem of developing countries but also of the developed countries. According to researchers, over 130 million people in Europe suffer from exposure to noise levels above 65 dB(A) [2].…”
Section: Introductionmentioning
confidence: 99%